ANALISIS PEMBELAJARAN ONLINE PADA PROGRAM STUDI TATA HIDANGAN DI AKADEMI KOMUNITAS MANAJEMEN PERHOTELAN INDONESIA - Tari, Nirmala; Oktaviani, Laras (Jurnal Manajemen Pelayanan Hotel, 2022)
The Covid-19 pandemic has forced the teaching and learning process to be done online. This of course requires the readiness of lecturers and students to implement it because the characteristics of online learning are different from before. This study aims to determine the implementation of online learning. This research is a quantitative descriptive research conducted at AKA MAPINDO Dalung which focuses on the tourism study program. The subjects of this study were 18 lecturers spread across all study programs. Meanwhile, the object of this research is a) the quality of the implementation of online learning, b) student behavior and c) the obstacles faced in online learning. Data were collected using a questionnaire. Furthermore, the data obtained were analyzed quantitatively by calculating the average which was then confirmed into the benchmark reference assessment (PAP). The results showed a) the quality of online learning was categorized as quite good with an average score of 2.92, b) the behavior of students participating in online learning was categorized as quite good with an average score of 2.79 and c) there were various problems and obstacles found during the implementation. online learning which is divided into 8 components, namely: learning organization, learning delivery, learning management, facilities and techniques, student activities, student creativity, interaction patterns and seriousness. Keywords: analysis, online learning